The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1465-3362.2009.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the implementation of a screening and brief intervention program for alcohol risk in primary health care: An experience in Brazil

Abstract: The barriers and facilitators were related to two main factors: organisational culture and personal attitudes. The action research provided the opportunity to bridge the gap between research and practice, but it also showed that SBI faces significant challenges before it can be implemented as a routine procedure in PHC settings in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
2
27
1
4
Order By: Relevance
“…Other authors from Brazil reported factors other than the ones previously cited, including some discomfort in dealing with the issue, a focus on substance dependence treatment, replacement of managers and professionals during the implementation process, other priorities, and difficulties in patient referrals to other services (Amaral et al, 2010). Some of these barriers were also found in the present study.…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…Other authors from Brazil reported factors other than the ones previously cited, including some discomfort in dealing with the issue, a focus on substance dependence treatment, replacement of managers and professionals during the implementation process, other priorities, and difficulties in patient referrals to other services (Amaral et al, 2010). Some of these barriers were also found in the present study.…”
Section: Discussioncontrasting
confidence: 39%
“…To change the professionals' attitudes about substance use issues and improve the efficacy of the implementation process, some strategies may be proposed: (1) the need for more intensive practical training (Gonçalves, 2005;Holmqvist et al, 2008;Ronzani, et al, 2005;Ronzani et al, 2008b;Souza-Formigoni et al, 2008, Amaral et al, 2010, (2) constant attendance to increase the involvement of healthcare professionals (Anderson et al, 2003, Amaral et al, 2010, (3) introducing methods of detection and intervention into the curricula and continuing education programs in health-related schools (Holmqvist, et al2008), and (4) improving the motivation for preventive strategies (Ronzani et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have identified impediments to Screening and Brief Intervention (SBI) implementation in health-care settings in a variety of countries, including Finland [8,9], Sweden [10,11], Denmark [12], Norway [13], Australia [14] and Brazil [15]. Challenges to conducting SBI include time constraints, the need to focus upon more medically urgent issues, poor training, negative provider attitudes and perceptions of role incompatibility [8,[16][17][18].…”
Section: Sbirt Implementation Barriers and Facilitatorsmentioning
confidence: 99%